Smart Work: Benefit or Cost? - Elisa, Sabta; Rojuaniah, Rojuaniah (Journal of Accounting and Finance Management, 2024)
This research focuses on the importance of implementing Smart Work and Empowerment in improving job satisfaction and employee performance, especially in companies engaged in technology education. In today's digital era, companies are required to adapt to change and utilize technology to increase productivity. The purpose of this study was to analyze the effect of Smart Work and Empowerment on job satisfaction and employee performance in Edutech companies. The research method used is a quantitative approach with variable measurement consisting of two exogenous variables (Smart Work and Empowerment) and two endogenous variables (Job Satisfaction and Performance). Data was collected through questionnaires distributed to 190 employees. Descriptive analysis and regression analysis were used to test the proposed hypothesis. The results showed that there is an effect of Smart Work and Empowerment can increase job satisfaction. In addition, job satisfaction is also able to improve employee performance. The implementation of Smart Work can increase job satisfaction. While empowerment does not make employee performance increase. So with these results companies in the edutech industry should focus more on developing and implementing smart work policies. Then, companies in the edutech industry must be more active in implementing empowerment strategies. This can be done by giving employees more freedom and authority in making decisions related to their work.